If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 9 = 30 + -2x Reorder the terms: 9 + X = 30 + -2x Solving 9 + X = 30 + -2x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + X = 30 + -9 + -2x Combine like terms: 9 + -9 = 0 0 + X = 30 + -9 + -2x X = 30 + -9 + -2x Combine like terms: 30 + -9 = 21 X = 21 + -2x Simplifying X = 21 + -2x
| Y=-12-4*(-3) | | 1/3m+6=15 | | C^2-50=-23k | | 45+37=82 | | -2r+s+4t=-9 | | 3x-5*(-12-4x)=-9 | | 24=k^2-10k | | x+3/5=x+7/12 | | 17x-186=3x+5 | | n/2-20=6 | | x+7=-3x+4 | | 4x+114+2x-156=180 | | -5*w^2+51=6 | | -6*(2/3)+3 | | (2a^2-0.3)(2a^2+0.3)= | | x*8-66=2x | | -3*(2/3)+5=y | | -9+6x=5-x | | 2(x-3)+5=6x-4(-1+x) | | -6x+(-3x+5)=-1 | | 43=6(x*x)-5x | | 10+22/7 | | 22/7-78 | | 78-22/7 | | 5p+12=62 | | 58/16 | | 10x-4y=2 | | 22=6*(x*x)-5x-21 | | 10-2a=-1a+1 | | b/3=15 | | 22=6x*6x-5x-21 | | -3(4x+3)+4(-6x+1)=43 |